Abstracts of the 14th European Conference on Eye Movements 2007 - Reinhold Kliegl; R. Engbert (Bern Open Publishing, 2007)
The European Conference on Eye Movements, ECEM2007, is the 14th in a series of international scientific conferences dedicated to transdisciplinary research on eye movements. The series was initiated in 1981 by Rudolf Groner in Bern and is organized every second year by a group of European scientists active in eye movement research. This meeting in Potsdam is the third one in Germany, after Göttingen in 1987 and Ulm in 1997. The broad range of topics of the ECEM conferences attracts scientists from psychology, cognitive and visual neuroscience, computer science and related disciplines with interests from basic research to medical and applied aspects. Some 400 scientists from 27 countries, literally from around the world, have registered as participants of ECEM2007 and submitted over 300 oral and poster presentations.